Synthesis of enantiomerically-enriched N-aryl amino-amides via a Jocic-type reaction. Issue 44 (31st October 2018) - Hobson, Christian; Perryman, Michael S.; Kirby, Gavin; Clarkson, Guy J.; Fox, David J.
Graphical abstract: Highlights: Trichloromethyl ketones can be reduced in high enantiomeric excess via asymmetric transfer hydrogenation. Reduction product alcohols react with anilines and base to produce N -aryl aminoamides in high enantiomeric excess. Biphasic reaction conditions are vital for high stereoselectivity. Mixtures of aryl and secondary alkyl amines selectively produce dialkyl amides of alpha- N -aryl amino acids. Abstract: Enantiomerically-enriched secondary trichloromethyl-alcohols react with aryl amines to give enantiomerically-enriched α- N -arylamino-acid derivatives. The intermediate acid chlorides can react in situ with aryl or, regioselectively, with alkyl amines to give aryl or alkyl α- N -arylamino amides.